Pengaruh Attitude Toward Behavior dan Change Mechanisms terhadap Pengambilan Keputusan Vasektomi pada Suami - Lilik Choiriyah; Esti Yunitasari; Ilya Krisnana; Ucik Nurmalaningsih (Universitas Nahdlatul Ulama Blitar, 2026)
Decision making on contraceptive use is actually not only the responsibility of women, but also a shared responsibility with their husbands. It is important to understand the factors that influence husbands' decisions in using contraceptives, one of which is attitude towards behavior. The mechanism of attitude change is also very important to understand, because it can affect changes in husbands' contraceptive decision making. This study aims to identify how attitudes towards contraception affect the husband's decision-making process, as well as the role of attitude change mechanisms in shaping their involvement in family planning choices. This study is a quantitative study with a cross-sectional approach. The sampling technique was carried out randomly with multistage random sampling. The sample in this study was calculated based on the Yamahen formula so that 110 respondents were obtained. The results of this study indicate that husbands' attitudes towards contraception significantly influence their decision-making process regarding contraceptive use. Positive attitudes towards contraception are associated with greater involvement in decision making and a higher likelihood of using contraception. Attitude change mechanisms, such as information from health care providers and discussions with partners, play an important role in changing husbands' perspectives, which ultimately lead to more supportive decisions regarding family planning. These findings highlight the importance of targeting attitude change in interventions aimed at increasing community participation in conservation decision-making.